A Development of Ethanol/Percarbonate Membraneless Fuel Cell. (29th May 2014) - Priya, M.; Arun, A.; Elumalai, M.; Kiruthika, S.; Muthukumaran, B.
Abstract : The electrocatalytic oxidation of ethanol on membraneless sodium percarbonate fuel cell using platinum electrodes in alkaline-acidic media is investigated. In this cell, ethanol is used as the fuel and sodium percarbonate is used as an oxidant for the first time in an alkaline-acidic media. Sodium percarbonate generates hydrogen peroxide in aqueous medium. At room temperature, the laminar-flow-based microfluidic membraneless fuel cell can reach a maximum power density of 18.96 mW cm −2 with a fuel mixture flow rate of 0.3 mL min −2 . The developed fuel cell features no proton exchange membrane. The simple planar structured membraneless ethanol fuel cell presents with high design flexibility and enables easy integration of the microscale fuel cell into actual microfluidic systems and portable power applications.